Impact of Ethical Leadership and Caring Work Climate on Turnover Intention of Health Care Professionals Mediating Role of Emotional Exhaustion - Anum Nawazish Ali, Sehrish Shahid, Maria Kanwal, Qurat-Ul-Ain Rasheed, Muhammad Usman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To examine the mediating relation of emotional exhaustion as well as moderating function of caring climate in such relationships. Study Setting: Health care providers in government hospitals (such as Lahore General Hospital, Mayo Hospital, Services Hospital, Nishtar Hospital, Multan) as well as private hospitals (such as Fatima Memorial Hospital, Shalamar Hospital, Doctors Hospital, National Hospital, Bakhtawar Amin Hospital, Multan) and health care centres in Lahore (such as the latter two) are included in this group. The health care providers are also included in this group. Study Duration: This study was conducted from period of 1st September to 1st December, 2020 in the selected Hospitals. Materials and Methods: In order to acquire data, a sampling method was used. Google forms were used to collect data online. A total of 105 health care professionals from Lahore's health care organisations participated in the survey. Process macro model 8 shows that ethical leadership is critical to assessing the variations in emotional tiredness and turnover intention, whereas the ethical environment has a negligible moderating impact on the changes in turnover intention. Exhaustion mediated the influence of ethical leadership on turnover intention, according to the findings. Results: The findings show that the ethical conduct of higher management is critical because workers' perceptions of an ethical leadership are based on the ethical beliefs of managers, and their sincere and truthful conduct is an important influence in shaping the organisational environment and thus influencing the employees' turnover intention. Aside from future research directions, the theoretical and practical consequences and constraints of the discussion are also contested. Conclusion: According to the findings of this study, the influence of ethical leadership on employee turnover is totally mediated by emotional weariness. There is a correlation between ethical leadership and the desire to leave the company. The association between ethical leadership and emotional weariness is also diminished. Furthermore, this study indicated that emotional irritation and turnover intention are linked in a positive manner.